"My hair, my crown". Examining black Brazilian women's anti-racist discursive strategies on social media. Issue 3 (1st September 2020) - Trindade, Luiz Valério de Paula
ABSTRACT: For a long time, Brazil has fostered the image of a post-racial society; however, data reveals that: a) racism against black women remains strongly ingrained in the collective mind-set, b) social media has become a breeding ground for the construction and dissemination of racist ideologies, and c) black women encompass the predominant target of racist discourses on social media. Thus, this qualitative study explores anti-racist discourses fostered by black Brazilian women on social media. Employing critical discourse analysis in a selection of publicly available Facebook posts, the study reveals that narratives praising an Afro hairstyle embody a relevant political positioning resisting Brazil's deep-seated gendered racism. They aim, first, to challenge Brazil's hegemonic "whitened" beauty standard; second, to convey a renewed perception of black esthetics as a legitimate source of ethnic identity; and, finally, they represent a strong symbolic element to manifest black women's agency and empowerment.